2012
DOI: 10.1002/jhm.1921
|View full text |Cite
|
Sign up to set email alerts
|

Nurse‐pharmacist collaboration on medication reconciliation prevents potential harm

Abstract: The adsorption capacity of a shale gas reservoir is mainly determined by the isothermal adsorption experiment. In this study, the building conditions and performances of seven single‐component and five multi‐component adsorption models were compared and analyzed. The results show that most shale gas reservoir adsorption characteristics obey those of type I on the macroscopic scale. The adsorption isotherms of single components can be described by the Langmuir‐Freundlich, Langmuir, and Toth models. The revised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 38 publications
0
49
0
1
Order By: Relevance
“…This highlights the desperate need for systems and structures in place that allow for ongoing medication reconciliation outside of the typical healthcare setting. Interprofessional programs that include pharmacist review in the reconciliation process are demonstrating favorable results in both hospital and community settings (Cumbler, Carter, & Kutner, 2008; Feldman et al, 2012; Reidt et al, 2014; Vogelsmeier, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the desperate need for systems and structures in place that allow for ongoing medication reconciliation outside of the typical healthcare setting. Interprofessional programs that include pharmacist review in the reconciliation process are demonstrating favorable results in both hospital and community settings (Cumbler, Carter, & Kutner, 2008; Feldman et al, 2012; Reidt et al, 2014; Vogelsmeier, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…However, medication discrepancies remain prevalent. For example, studies of medication discrepancies on admission to the hospital range from 22 to 70 percent (Feldman et al, 2012; Hellstrom, Bondesson, Hoglund, & Eriksson, 2012; Kilcup, Schultz, Carlson, & Wilson, 2013; Pourrat et al, 2013; Unroe et al, 2010; Wong et al, 2008; Ziaeian, Araujo, Van Ness, & Horwitz, 2012), admission to the nursing home post hospitalization were reported to be 86% (Boockvar, Carlson LaCorte, Giambanco, Fridman, & Siu, 2006) and at discharge to home from skilled nursing facility 90% of patients were found to have a drug-related problem in their medication regimen (Delate, Chester, Stubbings, & Barnes, 2008). Examination of medication lists provided by patients during an emergency department visit revealed that 80% contained a discrepancy error (Caglar, Henneman, Blank, Smithline, & Henneman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The significant finding that the number of medications was positively correlated with medication discrepancies was similar to previous work with inpatient medication reconciliation. 30 Overall, a home visit after hospital discharge for chronically ill patients taking multiple medications should not be underestimated. In 2013, the Affordable Care Act provides reimbursement for transitional care interventions 31 initiated by the primary care provider; however, hospitals that are not reimbursed for 30-day readmission receive no funding for transitional care interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, pharmacist involvement in medication reconciliation showed decreased medication errors and improved patient outcome [12,13]. Another study revealed nurse-pharmacy communication can significantly reduce medication errors [14]. Similarly, interdisciplinary approach between hospital, nursing home and pharmacy in the implementation of medical reconciliation has been shown to improve outcome especially those with chronic conditions [15].…”
Section: Discussionmentioning
confidence: 99%